2020
DOI: 10.3389/fimmu.2020.00534
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Roles of NDR1/2 in Infection and Inflammation

Abstract: The nuclear Dbf2-related (NDR) kinases NDR1 and NDR2 belong to the NDR/LATS (large tumor suppressor) subfamily in the Hippo signaling pathway. They are highly conserved from yeast to humans. It is well-known that NDR1/2 control important cellular processes, such as morphological changes, centrosome duplication, cell proliferation, and apoptosis. Recent studies revealed that NDR1/2 also play important roles in the regulation of infection and inflammation. In this review, we summarized the roles of NDR1/2 in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…The Hippo pathway key effectors, YAP and/or TAZ, were reported to be mediators or regulators of many inflammatory processes 72 74 . Furthermore, the role of other components of the Hippo pathway, including NDR1/2 75 and MST1 76 in inflammation has been emerging within recent years.…”
Section: The Hippo Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…The Hippo pathway key effectors, YAP and/or TAZ, were reported to be mediators or regulators of many inflammatory processes 72 74 . Furthermore, the role of other components of the Hippo pathway, including NDR1/2 75 and MST1 76 in inflammation has been emerging within recent years.…”
Section: The Hippo Pathwaymentioning
confidence: 99%
“…The Hippo pathway key effectors, YAP and/or TAZ, were reported to be mediators or regulators of many inflammatory processes [72][73][74] . Furthermore, the role of other components of the Hippo pathway, including NDR1/2 75 and MST1 76 in inflammation has been emerging within recent years. A prototypical proinflammatory cytokine, IL-6 77 , was found to potently activate YAP and Notch by binding its co-receptor gp130 9 .…”
Section: Hippo and Pathways Involved In Inflammationmentioning
confidence: 99%
“…The salient observation in this regard is the proteolytic cleavage of host PKs involved in innate immunity by HIV-1 PR. Nuclear Dbf2-related (NDR) kinases, NDR1 and NDR2 are essential PKs instrumental in regulating PRR and cytokines in innate immunity ( Ye et al, 2020 ) and HIV-PR has been shown to cleave both NDR1 and NDR2 ( Devroe et al, 2005 ). Similarly, receptor interacting protein kinases (RIPK) RIPK1 and RIPK3 are involved in eliminating virus infected cells through necroptosis and have also been shown to mediate type 1 IFN signaling for this purpose ( Rajput et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dbf2p-related kinase 1 (NDR1) in the biomembrane-localized protein kinase belongs to the family of NDR-LATS protein kinases. It can positively regulate centrosome replication in a non-dependent manner, and participates in cell apoptosis, cycle regulation, and biological processes, such as autophagy [ 9 ]. Studies have confirmed that, when pathogenic microorganisms invade, inducing the expression of NDR1 can enhance the body’s resistance to pathogenic microorganism infection [ 10 ].…”
Section: Introductionmentioning
confidence: 99%